The Effectiveness of Non-Litigation Resolution for Recurrent Domestic Violence And Efforts to Address it in Kupang City - Louise Marie Gere Kopa; Rudepel Petrus Leo; Deddy R. Ch. Manafe (Universitas Mataram, 2026)
Domestic violence is a human rights violation that continues to occur frequently and tends to be recurrent, indicating that existing response mechanisms are not yet optimal. One approach used in addressing domestic violence is non-litigious resolution through mediation, counseling, and psychological support. This study aims to analyze the effectiveness of non-litigious resolution for cases of recurring DV in Kupang City and to examine the mitigation efforts undertaken to reduce the incidence of recurring violence. This study employs an empirical legal approach using mixed methods. Primary data were collected through questionnaires and interviews with 60 respondents—comprising 30 victims and 30 perpetrators of repeated domestic violence—as well as interviews with law enforcement officials and relevant institutions, namely the Kupang City DP3A, LBH APIK NTT, and Rumah Harapan GMIT. Secondary data were obtained through a literature review of relevant laws and regulations and academic literature. The research findings indicate that non-litigation resolution is effective in reducing the intensity of violence and aiding victims’ psychological recovery in the short term. However, long-term effectiveness remains limited due to perpetrators’ low willingness to change, victims’ economic and social dependence, weak post-resolution monitoring, and deeply ingrained patterns of violence. Therefore, addressing recurring domestic violence requires an integrated approach through the combination of non-litigation and litigation mechanisms, institutional strengthening, victim empowerment, and continuous monitoring. The findings of this study are expected to serve as input for the government and relevant agencies in formulating more effective and sustainable policies for addressing domestic violence.